Student Data Security Optimization using Multiple Cryptography to Improve E-Campus Services - Azhari, Mulkan; Riza, Ferdy; Maulana, Halim (Blend Sains Jurnal Teknik, 2025)
Data security is a critical aspect of e-Campus services, which manage student information. However, the risks of data breaches and hacking pose significant challenges, undermining user trust. This study aims to optimize student data security by implementing multiple cryptographic methods that combine Advanced Encryption Standard (AES) and Rivest-Shamir-Adleman (RSA) algorithms. The research methods include analyzing current security vulnerabilities, developing a security model based on algorithm combinations, and testing its effectiveness through Avalanche Effect measurement, process time evaluation, and user satisfaction surveys. The results indicate that the AES and RSA combination provides stronger protection against security threats, achieving an Avalanche Effect value of 52,36% while ensuring confidentiality, integrity, and data authentication. This implementation also maintains process efficiency, making it suitabble for use in e-Campus environments. This study not only offers a practical solution to enhance data security but also provides implementation guidelines that can be adopted by other higher education institutions.